Visualising the Dispersion of Particles Within a Functionally Graded Material - Powell, Daniel (Cranfield University, 2022)
Functionally graded materials (FGMs) are designed to carefully alter material properties along a selected axis. This image shows FGMs created through mixing varying percentage volumes of high-density tungsten powder (in orange) with a low-viscosity epoxy (in white). Black regions show pores. As the epoxy cures the tungsten particles settle at various depths under gravity, notably in the 1%, 5% and 10% samples. Whilst there are multiple uses for FGMs, this research investigates if they could control the passage of damaging shock waves through a ceramic armour system, especially at the interlayer between a ceramic and metal.
Keywords: Functionally Graded Materials; Ceramic armour; Interlayers; DSDS2022; DSDS2022 Digital Image